Uma Investigação Sobre as Expectativas dos Estudantes e o seu Grau de Satisfação em Relação ao Curso de Ciências Contábeis - Umbelina Cravo Teixeira Lagioia (Revista Contemporânea de Contabilidade, 2007)
The purpose of this article was to investigate the expectations of Accounting students when they started the course so as to verify whether such expectations were maintained or changed during the course, as well as their level of satisfaction with the same. An empirical methodological approach was used through an exploratory research, with application of questionnaires. 324 students from all periods of the course form the sample. The no-parametric statistical qui-square test was used. The three main expectations were, preferentially: to try a public contest, to work in enterprises and to work in their own businesses. As to the level of satisfaction, the students declared to be satisfied with the course.